2022
DOI: 10.1039/d2an00163b
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive sensing of alkaline phosphatase and γ-glutamyltranspeptidase activity for tumor imaging

Abstract: Alkaline phosphatase (ALP) and γ-Glutamyltranspeptidase (GGT) are regarded as two important biomarkers in several human cancers. There are many probes for ALP or GGT detection but no probe was reported...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Of course, substrates for use with other approaches are available too. These include bioluminescence, [32] electrochemistry, [33] UV‐Vis spectroscopy, [34] Raman spectroscopy and surface‐enhanced (resonance) Raman spectroscopy (SERS and SERRS), [35] chemical exchange saturation transfer magnetic resonance imaging (CEST MRI), [36] electron paramagnetic resonance (EPR) spectroscopy, [37] and 19 F nuclear magnetic resonance (NMR) spectroscopy [38] …”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, substrates for use with other approaches are available too. These include bioluminescence, [32] electrochemistry, [33] UV‐Vis spectroscopy, [34] Raman spectroscopy and surface‐enhanced (resonance) Raman spectroscopy (SERS and SERRS), [35] chemical exchange saturation transfer magnetic resonance imaging (CEST MRI), [36] electron paramagnetic resonance (EPR) spectroscopy, [37] and 19 F nuclear magnetic resonance (NMR) spectroscopy [38] …”
Section: Detection Methodsmentioning
confidence: 99%
“…[31] Of course, substrates for use with other approaches are available too. These include bioluminescence, [32] electrochemistry, [33] UV-Vis spectroscopy, [34] Raman spectroscopy and surface-enhanced (resonance) Raman spectroscopy (SERS and SERRS), [35] chemical exchange saturation transfer magnetic resonance imaging (CEST MRI), [36] electron paramagnetic resonance (EPR) spectroscopy, [37] and 19 F nuclear magnetic resonance (NMR) spectroscopy. [38] Although many options are available, a limitation shared by these methods is their reliance on the inherent properties of a particular substrate or its product to generate a signal change depending on the instrument being used to follow the reaction.…”
Section: Detecting Non-phosphate Products From Signalgenerating Subst...mentioning
confidence: 99%
“…Yang et al developed a novel BL biosensor for sensing the activity of two important analytes namely, alkaline phosphatase (ALP) and γ-glutamyltranspeptidase (GGT) in vitro and in vivo. 114 The designed platform was constructed for real-time monitoring and specific cancer visualization through the cocleavage of the two analytes (ALP and GGT). They constructed the BL probe based on using D-luciferin which contains p-hydroxymethylphenyl and phosphate as selfcleavable moieties for the assay of ALP and GGT, respectively.…”
Section: Bl Probes For the Detection Of Enzyme Activitiesmentioning
confidence: 99%
“…Yang et al developed a novel BL biosensor for sensing the activity of two important analytes namely, alkaline phosphatase (ALP) and γ-glutamyltranspeptidase (GGT) in vitro and in vivo . The designed platform was constructed for real-time monitoring and specific cancer visualization through the cocleavage of the two analytes (ALP and GGT).…”
Section: Bl Imaging Applicationsmentioning
confidence: 99%
“…19 Similarly, studies have shown the ALP-triggered self-assembly of anticancer drug etoposide, ALP activatable bioluminescent probe for tumor imaging, and a trident molecule to suppress tumour metastasis. [20][21][22] Extensive studies were also carried out in the regime of ALP-mediated dephosphorylation of thiophosphopeptides and phosphopeptides, the dephosphorylated peptides self-assembling into highly cytotoxic nanoribbons and nanofibers in ALP overexpressed cancer cells. [23][24][25] Recently, extracellular ALP-assisted selfassembly and further GSH-mediated disassembly of platinum prodrug were also reported.…”
Section: Introductionmentioning
confidence: 99%